An application of multi-scale remote sensing in estimating grass nutrient limitation as measured by a ratio of Nitrogen and Phosphorus in a savanna ecosystem - Ramoelo, Abel (University of Pretoria, 2023)
Dissertation (MSc (Geoinformatics))--University of Pretoria 2023.